2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354101
|View full text |Cite
|
Sign up to set email alerts
|

Transferring embodied concepts between perceptually heterogeneous robots

Abstract: Abstract-This paper explores methods and representations that allow two perceptually heterogeneous robots, each of which represents concepts via grounded properties, to transfer knowledge despite their differences. This is an important issue, as it will be increasingly important for robots to communicate and effectively share knowledge to speed up learning as they become more ubiquitous. We use Gärdenfors' conceptual spaces to represent objects as a fuzzy combination of properties such as color and texture, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This paper presents the transition from the theoretical research developed earlier (e.g., [6][7][8][9][10]) to a practical working architectural implementation of Gardenfors conceptual spaces to a team of completely perceptually heterogeneous robots. Using sensors being developed by the Army's Microautonomous System Technology program and their surrogates, the abstract sensor layer (ASL) and conceptual space component of the overall system architecture has been implemented and tested, demonstrating the viability of this concept in the context of a biohazard search and detection mission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper presents the transition from the theoretical research developed earlier (e.g., [6][7][8][9][10]) to a practical working architectural implementation of Gardenfors conceptual spaces to a team of completely perceptually heterogeneous robots. Using sensors being developed by the Army's Microautonomous System Technology program and their surrogates, the abstract sensor layer (ASL) and conceptual space component of the overall system architecture has been implemented and tested, demonstrating the viability of this concept in the context of a biohazard search and detection mission.…”
Section: Discussionmentioning
confidence: 99%
“…We continue to exploit our novel approach to this problem that leverages our significant prior work [6][7][8][9][10] in the conceptual spaces framework developed by Gardenfors [4,1]. In this paper we focus on the architectural design and implementation issues associated with widely heterogeneous micro-robots that are tasked for specific missions.…”
Section: Introductionmentioning
confidence: 99%
“…This paper builds upon our previous work and shows that a hierarchical concept representation can be used to facilitate the fusion of concepts once the robots determine which of the representation's lower-level building blocks are shared. Previously, we have shown that the mappings between properties of two robots can be learned using real-robot data obtained in a shared context [5], and we have demonstrated the transfer of concepts from one robot to another in realistic 3D simulation experiments [6]. We have also shown that the abstraction of data through higher-level properties aids both learning and knowledge transfer, in real experiments where support vector machine classifiers are used to combine properties and classify objects [7].…”
Section: Related Workmentioning
confidence: 93%
“…We begin by formally describing the framework and demonstrating how raw sensory data is abstracted into higher levels properties, which are then combined to represent concepts [5,6]. Validation of this framework for the classification of real objects using sensor obtain from real-robot experiments are described in the next section.…”
Section: Using Conceptual Spaces With Real Robot Datamentioning
confidence: 99%
“…Despite the clear focus on the semantic aspect, the works mentioned above are lacking a cooperative multi robot aspect, which we try to also capture in our current work. This specific aspect of transferring embodied concepts between perceptually heterogeneous robots has been studied in 19 , where the different perceptually heterogeneous embodiments communicate and effectively share knowledge that they have learned through individual experiences. Their approach is based on communication and knowledge exchange via social interaction, where properties of the world can be grounded differently in different robots.…”
Section: Related Workmentioning
confidence: 99%